The Evaluation of Communicative Language Teaching - Wang, Sijia (Scientific Journal of Technology, 2025)
This paper briefly explain the application of Communicative Language Teaching(CLT) in China and discuss the CLT from the perspective of its characteristics and practice in China. It aims to provide a critical analysis of CLT in language teaching of China.